2016
DOI: 10.2147/copd.s97924
|View full text |Cite
|
Sign up to set email alerts
|

Differences in outcomes between GOLD groups in patients with COPD in the TIOSPIR® trial

Abstract: BackgroundThe aim of this study was to evaluate whether Global Initiative for Chronic Obstructive Lung Disease (GOLD) classification could predict mortality risk factors and whether baseline treatment intensity would relate to mortality within each group, using data from TIOSPIR®, the largest randomized clinical trial in COPD performed to date.MethodsA total of 17,135 patients from TIOSPIR® were pooled and grouped by GOLD grading (A–D) according to baseline Medical Research Council breathlessness score, exacer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Unexpectedly, less than 22 % of the admitted patients were in GOLD stage I/II and were hospitalized for different reasons including chest pain, cancer, decompensation, heart disease, dyspnea and infections. This reinforces the fact that those in these GOLD classes are vulnerable and at risk of exacerbation and death despite having better spirometry [21]. Another interesting study, reported a shift from the 2007 1-4 GOLD classification to the 2011 A-D classification.…”
Section: Discussionsupporting
confidence: 64%
“…Unexpectedly, less than 22 % of the admitted patients were in GOLD stage I/II and were hospitalized for different reasons including chest pain, cancer, decompensation, heart disease, dyspnea and infections. This reinforces the fact that those in these GOLD classes are vulnerable and at risk of exacerbation and death despite having better spirometry [21]. Another interesting study, reported a shift from the 2007 1-4 GOLD classification to the 2011 A-D classification.…”
Section: Discussionsupporting
confidence: 64%
“…Patients with severe to very severe COPD have worse health status [2], higher risk of hospitalised exacerbations, higher acute care burdens [1,3] and higher mortality rates than patients with mild to moderate disease [4][5][6][7]. This was also shown in the TIOSPIR (Tiotropium Safety and Performance in Respimat) trial, where the risks of respiratory-related deaths and hospitalised exacerbations were greater in GOLD (Global Initiative for Obstructive Lung Disease) C or D patients than in GOLD A patients [8]. Better control of exacerbation frequency and severity could slow disease progression and reduce hospitalisation [9,10], especially in patients with severe COPD who encounter difficulties in managing their disease on a daily basis.…”
Section: Introductionmentioning
confidence: 97%
“…Treatment outcome would be poorer if the grade of COPD is poorer. 18 Inhaled steroid and baseline FEV1% favoured a better outcome in the group of patients on single inhaler. All the patients on single inhaler used spacer whereas only 70% of the patients on two inhalers used spacer.…”
Section: Discussionmentioning
confidence: 92%